Comparison of six-month outcome of patients initially treated for acute deep vein thrombosis with a low molecular weight heparin Certoparin at a fixed, body-weight-independent dosage or unfractionated heparin - Harenberg, Job; Riess, Hanno; Buller, H. R.; Brom, Joachim; Weidinger, Gottfried; Huisman, M. V. (Haematologica, 2003)
BACKGROUND AND OBJECTIVES: Body weight-adjusted subcutaneous low molecular weight heparin (LMWH) has been proven to be more effective and safer than aPTT-adjusted intravenous unfractionated heparin (UFH) for the initial treatment of patients with acute symptomatic deep venous thrombosis (DVT) based on analyses pooling the results of studies with different LMWHs. We investigated whether these findings hold for a particular LMWH by pooling the results of two independent studies. DESIGN AND METHODS: Patients with acute symptomatic proximal DVT (n=1758), proven by ascending phlebography or compression ultrasound, received either a fixed, body weight independent dose of 8,000 IU Certoparin b.i.d. (n=893) for 8.6 days or intravenous UFH (n=865) adjusted to an 1.5 to 3.0-fold prolongation of the aPTT for 12.0 days both followed by vitamin K-antagonists for 6 months. RESULTS: Venous thromboembolism (VTE) re-occurred in 5.1% and 3.1% (RRR 0.62, CI 0.39-0.98, 2p=0.04), major bleeding in 3.5% and 1.9% (RRR 0.55, CI 0.31-0.99, 2p=0.05), mortality in 3.6% and 2.1% (RRR 0.59, CI 0.34-1.04, 2p=0.08), and the composite outcome of all three events in 10.3% and 6.3% (RRR 0.61, CI 0.44 to 0.84, 2p=0.002) of patients at 6 months initially randomised to UFH and LMWH, respectively. INTERPRETATION AND CONCLUSIONS: The initial treatment of acute DVT with a fixed dose of the LMWH, certoparin, is more effective in reducing, over 6 months, the re-occurrence of VTE and the composite outcome of recurrent VTE, major bleeding, and mortality without any relation of the bodyweight of the patients to recurrent venous thromboembolism or major bleeding complications.